Nonlinear observer based PI sliding surface of adaptive sliding mode control for boost converter in PV system - Ramadhani Kurniawan Subroto; Lunde Ardhenta; Eka Maulana (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
In photovoltaic system, solar energy is not able to be directly utilized to the grid. This is because the the generated output voltage from solar array are fluctuating depends on the environmental condition, such as the intensity of solar irradiance and temperature. Any changes from those variables will affect the generated output voltage. Boost converter is one type of power converter that is able to regulate the output voltage of solar array to dc grid. However, the dynamics of boost converter is nonlinear and non-minimum phase. Therefore, it requires an appropriate control method that can force the output voltage follows the desired reference voltage, by considering the fluctuation of environmental conditions and loads. To reduce the number of sensors and cost investment, nonlinear observer technique is employed to estimate the input voltage and load variations. By considering this problem, this paper is aimed at designing nonlinear observer based on adaptive sliding mode control with PI sliding surface for boost converter. The stability of proposed system is investigated through analytical and simulation proof. As comparison with PID controller, the performance of proposed system has produced Integral Absolute Error (IAE) about 7 times smaller than PID controller when it is tested under various conditions.